Aging as a Productive Process: A Critical Analysis of Aging Policy in Newfoundland and Labrador, Canada. Issue 1 (2nd January 2022) - Mandville-Anstey, Sue Ann; Ward, Pamela; Cameron, Erin; Browne, Marlene; Foley, Holly
ABSTRACT: There has been a growing focus on healthy aging in the political agenda. Discourses contained within policy documents have the potential to shape our notions of healthy aging and well-being. This comprehensive critical document analysis of provincial aging policies in Newfoundland and Labrador (2006–2015) contributes to a larger research study exploring aging women's notions of health and the body in relation to the aging process. The findings highlight how healthy aging discourses focus on the concept of productivity and how a certain type of health is required for ongoing contribution. The paper concludes by arguing that if healthy aging is framed around one's ability to remain productive, notions of health will remain limited to an externalized measure of output versus subjective experience of well-being.